Odpowiedzi

2010-03-11T19:42:17+01:00
Zadanie 9
a) =-3xy³+3xy-2xy³+xy= -5xy³+4xy= -5×(-1)×2³+4×(-1)×2=32
b)=48a²-10a+4a+a²=49a²-6a= 49×(1/7)²-6×1/7=1-6/7=1/7
c)=-12√c+c-8c+13√c=√c-7c=√4-7×4=2-28=-26
zadanie 10
a)=-y+6x-z=-6+6×(-2)-(-3)=-15
b)=-9y-6z+x+1=-9×(-1)-6×2-0.5+1=-2.5
c)=9y-7y-x+6x-7y=-5y+5x=-5×3+5×(-2)=-25
d)=6a-8b-0.7-6.9-a+5b=5a-3b-7.6=5×0.2-3×0.1-7.6=-6.9
e)=0.5abc-4ab-2abc-bc+5ab=-1.5abc-bc+ab=-1.5×(-2)×0.5×(-4)-0.5×(-4)+(-2)×0.5=-6+2-1=-5
Najlepsza Odpowiedź!
2010-03-11T20:32:16+01:00
9.
a)-3xy³+3xy-(2xy³-xy)= -3×-1×2³-(2×-1×2³-(-1)×2)=24-(-16)-(-2)=42
b)-(-48a²+10a)-(-4a-a²)=-(-48×(-1/7)+10×(-1/7))-(-4×(-1/7)-(-1/7)²=6i6/7-1i3/7-4/7+1/7= 35/7=5
c)-(12√c-c)+(-8c+13√c)= -(12√4-4)+(-8×4+13√4)= -20 -6=-26

10.
a) -y+8x-z-2x=-6+8×-2-(-3)-2×(-2)=-15
b) -8y-4z+x-y-2z+1+=8-8-0,5+1-4+1= -2,5
c) 9y-(7y+x)+(6x-7y)= 27-19-33= -25
d) (6a-8b-0,7) - (6,9+a-5b) +1,8= (1,2-0,8-0,7)-(6,9+0,2-0,5) +1,8=-5,1
e) ½abc-(4ab+2abc)+(-bc+5ab)= 2-(-12)-3= 11